INOVASI KEBIJAKAN PROGRAM SANTRI MILINEAL CENTRE (SiMaC) DALAM UPAYA PENDUKUNG EKONOMI RAKYAT DI KOTA PROBOLINGGO - Husni Mubaroq,; Murtias Puji Astutik, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The growth of the business world in Indonesia has penetrated the era of globalization, so that the business world is required to continue to grow rapidly. Such conditions have led to the emergence of institutions that carry out business in all fields, one of which is Islamic boarding school learning institutions. Islamic boarding schools have a unique culture. Because the uniqueness of Islamic boarding schools is classified into certain sub-cultures in Indonesian citizens. This type of research uses descriptive research with a qualitative approach. The focus of this research is the government and Islamic boarding schools in an effort to support the economy. The results of this study indicate that Islamic boarding schools are ready to compete with the global world. In addition to involving students, the pesantren also involves the surrounding community to help turn the wheels of the economy. The economic wheel cannot only run if it is not based on assistance or support from the community which is part of the economic development of the pesantren in addition to the pesantren community itself.